Speculative Investor Behavior and Learning - Morris, S. (Quarterly Journal of Economics, 1996)
As traders learn about the true distribution of some asset's dividends, a speculative premium occurs as each trader anticipates the possibility of reselling the asset to another trader before complete learning has occurred. Small differences in prior beliefs lead to large speculative premiums during the learning process. This phenomenon helps explain a paradox concerning the pricing of initial public offerings. The result casts light on the significance of the common prior assumption in economic models.